Anxiety and the Death Imagery of Desire (Global Journal of Human-Social Science, 2013)
The mockery that death seeks to wield over life is no better exemplified than in the risus sardonicus that seems to betray its own irrationality at the thought of being able to taunt us from beyond the grave. Such a grinning gripping looking awry seems to say to us, 'here too is your fate, you'll see, and the thought of your realization of it makes me mirthful!' The immediate reaction of the living is to pretend that we have not seen such a face, to ignore its remorseless stare, as one looks away from the portrait that follows us too closely-especially if the ancestor had a notorious reputation-perhaps the looking awry threatens us with the same historical fate through a contagious magic or action at a distance-or perhaps the woman in the painting is not as pretty as we might desire, or the man not as handsome, etc. But the face of death appears in many guises, and we must constantly attempt to think of something other than its presence, the elephant in the room that is as inconvenient as it is immovable: "We don't know how to deal with death, and so we ignore it as much and for us as long as possible. We concentrate on life